How a quartet of theatres plays under an acoustic perspective: A comparison between horseshoe shaped plans in Campania. Issue 3 (September 2022) - Bevilacqua, Antonella; Sukaj, Silvana; Ciaburro, Giuseppe; Iannace, Gino; Lombardi, Ilaria; Trematerra, Amelia
Many of the Italian Opera theatres built in small towns have not been deeply studied under an acoustic perspective compared to the most famous ones. This paper focuses the attention on small-sized theatres characterized by a horseshoe-shaped plan layout. The determination of the acoustic properties has been outlined by performing acoustic surveys inside each theatre. By analyzing the measured data, the results show comparable outcomes found inside the selected halls, with a negligible difference among them. Overall, all the four theatres have a good speech response, ranging between 0.60 and 0.74 in terms of sound transmission index (STI), with a small merit attributed to Benevento. These considerations should be combined with the sound perception with regard to the music performed inside these theatres. A trade-off between these two aspects has been well matched by the architects who were in charge to design these memorable places that nowadays are still impressive although not so many spotlights are given to them.